2019 IEEE Global Communications Conference (GLOBECOM) 2019
DOI: 10.1109/globecom38437.2019.9014026
|View full text |Cite
|
Sign up to set email alerts
|

Non-Stationary Polar Codes for Resistive Memories

Abstract: Resistive memories are considered a promising memory technology enabling high storage densities with inmemory computing capabilities. However, the readout reliability of resistive memories is impaired due to the inevitable existence of wire resistance, resulting in the sneak path problem. Motivated by this problem, we study polar coding over channels with different reliability levels, termed non-stationary polar codes, and we propose a technique improving its bit error rate (BER) performance. We then apply the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Channels with non-uniformity can be considered as channels with SNR variation [15] or non-stationary channels [9], [16]. These models have been studied in the ECC literature in the context of e.g., LDPC codes and Polar codes for storage applications [9], [15], [16]. However, these complex codes with long block length and high decoding latency (on the order µs [17]) are not compatible with the small decoding granularity and fast decoding requirements of the SCM applications.…”
Section: Channel Coding For Storage-class Memory (Scm) Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Channels with non-uniformity can be considered as channels with SNR variation [15] or non-stationary channels [9], [16]. These models have been studied in the ECC literature in the context of e.g., LDPC codes and Polar codes for storage applications [9], [15], [16]. However, these complex codes with long block length and high decoding latency (on the order µs [17]) are not compatible with the small decoding granularity and fast decoding requirements of the SCM applications.…”
Section: Channel Coding For Storage-class Memory (Scm) Applicationsmentioning
confidence: 99%
“…In an array with largely non-uniform device reliability, efficient ECC solutions must take this non-uniformity into consideration by either mitigating it or leveraging it. Channels with non-uniformity can be considered as channels with SNR variation [15] or non-stationary channels [9], [16]. These models have been studied in the ECC literature in the context of e.g., LDPC codes and Polar codes for storage applications [9], [15], [16].…”
Section: Channel Coding For Storage-class Memory (Scm) Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in [9], the authors proposed to use ECCs targeting the typical BER instead of the worst-case BER to improve system performance. In [10], the authors designed a non-stationary polar code targeting channels with different reliability levels, which are characterized empirically by simulations. Moreover, [10] also showed that using more precise channel modeling, i.e., using the binary asymmetric channel (BAC) instead of the binary symmetric channel (BSC), provides an order of magnitude improvement in BER, which proves the necessity of precise channel models.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far limited work has been done on error correction coding for ReRAM. In particular, a non-stationary polar coding scheme for ReRAM was proposed by [17], which is mainly aimed to address the raw bit error rate (BER) diversity among different bitlines, rather than tacking the sneak path interference. In [16], an across-array coding strategy is proposed, which assigns a codeword to multiple memory arrays.…”
mentioning
confidence: 99%